An Examination of the Stock Returns of TOP Partners During of the 2024 Paris Olympic Games - Timothy Koba (Journal of Applied Sports Management, 2025)
The International Olympic Committee generated $7.6 billion in revenue from 2017-2021, with 30% coming from The Olympic Partnership (TOP) Program marketing rights, which has grown from $96 million to $2.3 billion since 1985. In addition to the direct sponsorship costs, additional activation costs are incurred by the organization as they market, advertise, and highlight their product during the event they sponsor to achieve a financial return. The purpose of this study is to assess whether TOP partners outperform a matched non-partner during the 2024 Paris Olympic Games. This study utilizes an event study methodology to create three event windows related to the 11 trading days prior to, the 11 trading days during, and the 11 trading days post the 2024 Paris Olympic Games. The 14 TOP partners were matched with a non-partner to ascertain what effect TOP sponsorship had on the companies during these Olympic event windows using a multiple regression model. The results of the linear regression do not demonstrate a TOP effect for outperforming a non-partnering competitor. There was a 5.9% reduction in returns for tech companies prior to the Olympic Games, which taken together can provide potential trading strategies related to the Games.
Keywords: Sport Finance; Event Study; Sponsorship; Olympics